2006
DOI: 10.1590/s1516-44462006000200011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 5-HT2a/2c receptor agonist microinjected into central amygdaloid nucleus and median preoptic area on maternal aggressive behavior in rats

Abstract: The effect of 5-HT 2a/2c receptor agonist microinjected into central amygdaloid nucleus and median preoptic area on maternal aggressive behavior in rats Efeito sobre o comportamento materno agressivo de ratos da microinjeção do agonista seletivo de receptores 5-HT 2a/2c no núcleo central da amígdala e na área pré-óptica medial A b s t r a c t Objective: Much evidence supports the hypothesis that 5-hydroxytryptamine (5-HT) activation is related to the inhibition of aggression. We examined potentially pro-and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…These lines of evidence seem to be consistent with the serotonergic theory of anxiety disorder, even though conflicting reports can be found as well [Beckett and Marsden, 1997;Shaikh et al, 1997]. Interestingly, as for the opposite behavioral effects determined after HTR2C stimulation in the VTA and NAs reported before, stimulation of the HTR2C in the PAG is associated with anti-anxiety effect, whilst stimulation of HTR2C in the limbic forebrain (amygdala and hippocampus) has been reported to be associated with anxiety like or aggressive behavior [de Almeida et al, 2006;Cornelio and Nunes-de-Souza, 2007;Nunes-de-Souza et al, 2008]. These lines of evidence may suggest the presence of diverse HTR2C populations, or, better, the expression of HTR2C receptors in the surface of interneurons embedded in inhibitory or facilitative pathways in the midbrain and limbic forebrain respectively.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…These lines of evidence seem to be consistent with the serotonergic theory of anxiety disorder, even though conflicting reports can be found as well [Beckett and Marsden, 1997;Shaikh et al, 1997]. Interestingly, as for the opposite behavioral effects determined after HTR2C stimulation in the VTA and NAs reported before, stimulation of the HTR2C in the PAG is associated with anti-anxiety effect, whilst stimulation of HTR2C in the limbic forebrain (amygdala and hippocampus) has been reported to be associated with anxiety like or aggressive behavior [de Almeida et al, 2006;Cornelio and Nunes-de-Souza, 2007;Nunes-de-Souza et al, 2008]. These lines of evidence may suggest the presence of diverse HTR2C populations, or, better, the expression of HTR2C receptors in the surface of interneurons embedded in inhibitory or facilitative pathways in the midbrain and limbic forebrain respectively.…”
supporting
confidence: 77%
“…The role of the amygdala seems to be specific to the innate fear response since that this anxiety like behavior elicited by HTR2C agonists was undetectable when the ventral or dorsal hippocampus were stimulated [Cornelio and Nunes-de-Souza, 2007]. Consistently, an aggressive behavior was achieved after administration of an HTR2C agonist in the central nucleus of amygdala, in female rats selected at the 7th day after partum [de Almeida et al, 2006]. Maybe not surprisingly, HTR2C agonist effect in the basolateral amygdala-detected as a c-fos activation-is also associated with a diminished appetite in animal models [Somerville et al, 2007].…”
mentioning
confidence: 73%
“…Brunner et al (1999) reported that 5-HT 1B receptor knockout mother mice did not display pup retrieval deficits. Other studies found that 5-HT 1B and 5-HT 2A/2C receptors are involved in maternal aggressive behavior (De Almeida et al, 2005, 2006a, 2006b; Olivier et al, 1995; Veiga et al, 2007). Recently, Lerch-Haner et al (2008) reported that transgenic mouse dams with a specific disruption in serotonin transcription factor displayed profound maternal deficits (e.g., pup retrieval, pup nursing, nest building).…”
Section: Discussionmentioning
confidence: 95%
“…Together, these studies demonstrate a broad involvement of 5-HT 1 receptor-type signaling in modulating, mostly inhibiting, aggressive behavior. Local infusion of 5-HT 2A/2C receptor agonist into the corticomedial amygdaloid nucleus increases, but infusion into the dorsal PAG reduces aggression in female rats (de Almeida et al, 2005b(de Almeida et al, , 2006. Interestingly, orbitofrontal availability of 5-HT 2A receptors assessed through PET imaging is higher in personality disorder patients with physical aggression when compared with patients without aggression or healthy controls (Rosell et al, 2010).…”
Section: Mechanistic Insight On the Pa Establishment Of Perturbed Emomentioning
confidence: 99%